2020
DOI: 10.3346/jkms.2020.35.e272
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Ammonium Chloride on Ozone-induced Airway Inflammation: the Role of Slc26a4 in the Lungs of Mice

Abstract: Background: Exposure to ozone (O 3) induces neutrophilic inflammation and goblet cell hyperplasia in humans and experimental animals. Because the solute carrier family 26-member 4 (Slc26a4; pendrin) gene induces mucin production and intraluminal acidification in the airways, it was hypothesized to be a key molecule in O 3-induced airway injury. Thus, we evaluated the role of Slc26a4 and the protective effects of ammonium chloride (NH 4 Cl) in O 3-induced airway injury in mice. Methods: Six-week-old female BALB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Among them, nine genes (Gpnmb, Trem2, Clec4d, Slc26a4, Ear6, Cd300lf, Ctsd, Ptgir, and Tacc3) were upregulated in the APM group relative to the DEP group in a dosedependent manner. The top nine genes have important roles in lung inflammation, asthma, COPD, pulmonary fibrosis, and lung cancer [35][36][37][38][39][40][41][42][43] . In this study, we observed common lung inflammation in the DEP and APM groups through histological assessment, and the severity was higher in the APM group relative to the DEP group.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, nine genes (Gpnmb, Trem2, Clec4d, Slc26a4, Ear6, Cd300lf, Ctsd, Ptgir, and Tacc3) were upregulated in the APM group relative to the DEP group in a dosedependent manner. The top nine genes have important roles in lung inflammation, asthma, COPD, pulmonary fibrosis, and lung cancer [35][36][37][38][39][40][41][42][43] . In this study, we observed common lung inflammation in the DEP and APM groups through histological assessment, and the severity was higher in the APM group relative to the DEP group.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17A is known to induce goblet cell hyperplasia and mucus production, which are prominent features of airway diseases, such as COPD, asthma, and cystic fibrosis [28][29][30]43 . Moreover, IL-17A is known to stimulate upregulation of SLC26A4, an anion exchange protein which is known to induce goblet cell hyperplasia in human lung mucoepidermoid carcinoma cells and murine airway epithelial cells [44][45][46][47] . Interestingly, SLC26A4 was found to be elevated in serum 48 , endobronchial biopsies 49 , and lung tissues of asthmatics 45 , and inversely associated with percentage of forced expiratory volume in 1 s (FEV 1 %), suggesting its role in airway disease 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL-17A is known to stimulate upregulation of SLC26A4, an anion exchange protein which is known to induce goblet cell hyperplasia in human lung mucoepidermoid carcinoma cells and murine airway epithelial cells [44][45][46][47] . Interestingly, SLC26A4 was found to be elevated in serum 48 , endobronchial biopsies 49 , and lung tissues of asthmatics 45 , and inversely associated with percentage of forced expiratory volume in 1 s (FEV 1 %), suggesting its role in airway disease 48 . Our data shows that SLC26A4 is the most differentially expressed gene in response to IL-17A, suggesting its significant role in driving goblet cell hyperplasia in our model.…”
Section: Discussionmentioning
confidence: 99%